Long-term results of ipsilateral radiotherapy for tonsil cancer - Koo, Tae Ryool; Wu, Hong-Gyun (Radiation oncology journal, 2013)
WE EVALUATED THE EFFECTIVENESS AND SAFETY OF IPSILATERAL RADIOTHERAPY FOR THE PATIENT WITH WELL LATERALIZED TONSIL CANCER: not cross midline and <1 cm of tumor invasion into the soft palate or base of tongue. From 2003 to 2011, twenty patients with well lateralized tonsil cancer underwent ipsilateral radiotherapy. Nineteen patients had T1-T2 tumors, and one patient had T3 tumor; twelve patients had N0-N2a disease and eight patients had N2b disease. Primary surgery followed by radiotherapy was performed in fourteen patients: four of these patients received chemotherapy. Four patients underwent induction chemotherapy followed by concurrent chemoradiotherapy (CCRT). The remaining two patients received induction chemotherapy followed by radiotherapy and definitive CCRT, respectively. No patient underwent radiotherapy alone. We analyzed the pattern of failure and complications. The median follow-up time was 64 months (range, 11 to 106 months) for surviving patients. One patient had local failure at tumor bed. There was no regional failure in contralateral neck, even in N2b disease. At five-year, local progression-free survival, distant metastasis-free survival, and progression-free survival rates were 95%, 100%, and 95%, respectively. One patient with treatment failure died, and the five-year overall survival rate was 95%. Radiation Therapy Oncology Group grade 2 xerostomia was found in one patient at least 6 months after the completion of radiotherapy. Ipsilateral radiotherapy is a reasonable treatment option for well lateralized tonsil cancer. Low rate of chronic xerostomia can be expected by sparing contralateral major salivary glands.